Information systems - Steven Alter (Benjamin/Cummings, 1996)
This book presents a frameworkthat can be used to create a system summary to start the analysis of any information system. It defines the term information system and explains the relationship between information technology, information systems, and business processes. It discusses the applications and impacts of information systems, explains aspects of information technology covering computers and peripherals, software and programming, network and telecommunications. Finally, the book is closed by looking at the processes ralated to building these systems and keeping them operating